Application of GIS Technique to Evaluate the Groundwater Quality for Irrigation Purposes - Mufid Alhadithi (Tikrit Journal of Pure Science, 2018)
Geographic Information System (GIS) technique has been applied in the current study to produce irrigation water quality index (IWQI) map for the Karbala provenience in Iraq. For this purpose, hundred and twenty two (122) samples of groundwater have been collected for various sites of the study area. These samples have been analyzed for different elements that affect the irrigation water quality. Specifically, five chemicals parameters were used Electrical conductivity (EC), Cl-, HCO3-1, Na% and Sodium Absorption Ratio (SAR) to create the database of water quality which has been transferred to the GIS platform to produce a spatial distribution map of each parameter using reverse interpolation technique (IDW). The results of these parameters were also used to calculate irrigation water quality index values, and transferred to the GIS platform for the production of the irrigation water quality index map. Accordingly the groundwater in the studied area is unsuitable for irrigation except for a small part which represents 8 % of the total area that could be used with high permeability soils, which have the ability to carry a high proportion of salts.